Homelessness and integrated care: an application of integrated care knowledge to understanding services for wicked issues. Issue 1 (28th June 2021) - Clark, Michael; Cornes, Michelle; Whiteford, Martin; Aldridge, Robert; Biswell, Elizabeth; Byng, Richard; Foster, Graham; Fuller, James Sebastian; Hayward, Andrew; Hewett, Nigel; Kilminster, Alan; Manthorpe, Jill; et al.
Abstract : Purpose: People experiencing homelessness often have complex needs requiring a range of support. These may include health problems (physical illness, mental health and/or substance misuse) as well as social, financial and housing needs. Addressing these issues requires a high degree of coordination amongst services. It is, thus, an example of a wicked policy issue. The purpose of this paper is to examine the challenge of integrating care in this context using evidence from an evaluation of English hospital discharge services for people experiencing homelessness. Design/methodology/approach: The paper undertakes secondary analysis of qualitative data from a mixed methods evaluation of hospital discharge schemes and uses an established framework for understanding integrated care, the Rainbow Model of Integrated Care (RMIC), to help examine the complexities of integration in this area. Findings: Supporting people experiencing homelessness to have a good discharge from hospital was confirmed as a wicked policy issue. The RMIC provided a strong framework for exploring the concept of integration, demonstrating how intertwined the elements of the framework are and, hence, that solutions need to be holistically organised across the RMIC. Limitations to integration were also highlighted, such as shortages of suitable accommodation and the impacts of policies in aligned areas of the welfare state. Research limitations/implications: The data for this secondary analysis were not specifically focussed on integration which meant the themes in the RMIC could not be explored directly nor in as much depth. However, important issues raised in the data directly related to integration of support, and the RMIC emerged as a helpful organising framework for understanding integration in this wicked policy context. Practical implications: Integration is happening in services directly concerned with the discharge from hospital of people experiencing homelessness. Key challenges to this integration are reported in terms of the RMIC, which would be a helpful framework for planning better integrated care for this area of practice. Social implications: Addressing homelessness not only requires careful planning of integration of services at specific pathway points, such as hospital discharge, but also integration across wider systems. A complex set of challenges are discussed to help with planning the better integration desired, and the RMIC was seen as a helpful framework for thinking about key issues and their interactions. Originality/value: This paper examines an application of integrated care knowledge to a key complex, or wicked policy issue.